2021
DOI: 10.1002/tcr.202100208
|View full text |Cite
|
Sign up to set email alerts
|

Reported Catalytic Hydrofunctionalizations that Proceed in the Absence of Catalysts: The Importance of Control Experiments

Abstract: The enlarged landscape of catalysis lies in the heart of chemistry. As the journey has set a milestone in organic synthesis, its darker side has not entered into the limelight. Studies disclose that the reported reactions by using catalysts were also attainable in the absence of catalysts in many cases. This article presents a literature collection that includes the significance of control experiments in hydrofunctionalization reactions. Systematic analysis reveals that the catalysts are ambiguous and might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…For example, much less soluble potassium hydroxide led to any conversion only at elevated temperature (Table 1, entry 6). The catalyst‐free attempt was also carried out and proved the essential role of the main‐group catalysis (Table 1, entry 2, the results verified after 2 h and 24 h) [41] . Here, the reaction was performed in a brand‐new set of equipment (Schlenk tube and magnetic stirrer), which is highly important to exclude the influence of any transition metal impurities [42,43] .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, much less soluble potassium hydroxide led to any conversion only at elevated temperature (Table 1, entry 6). The catalyst‐free attempt was also carried out and proved the essential role of the main‐group catalysis (Table 1, entry 2, the results verified after 2 h and 24 h) [41] . Here, the reaction was performed in a brand‐new set of equipment (Schlenk tube and magnetic stirrer), which is highly important to exclude the influence of any transition metal impurities [42,43] .…”
Section: Resultsmentioning
confidence: 91%
“…The catalyst-free attempt was also carried out and proved the essential role of the main-group catalysis (Table 1, entry 2, the results verified after 2 h and 24 h). [41] Here, the reaction was performed in a brand-new set of equipment (Schlenk tube and magnetic stirrer), which is highly important to exclude the influence of any transition metal impurities. [42,43] Moreover, the lack of any conversion suggested no leaching of the alkali species from the glassware, which could act as potential cocatalysts in our catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments showed that other ruthenium sources were also active in this transformation (Table 1, entries 7–9), but gave inferior results. The catalyst‐free attempt was also carried out and proved the essential role of the main‐group catalysis (Table 1, entry 2, the result verified after 24 h) [30] . Here, the reaction was performed in a brand‐new set of equipment (Schlenk tube and magnetic stirrer), which is highly important to exclude the influence of any transition metal impurities [31,32] .…”
Section: Resultsmentioning
confidence: 94%
“…The catalyst-free attempt was also carried out and proved the essential role of the main-group catalysis (Table 1, entry 2, the result verified after 24 h). [30] Here, the reaction was performed in a brand-new set of equipment (Schlenk tube and magnetic stirrer), which is highly important to exclude the influence of any transition metal impurities. [31,32] We also demonstrated that our process can be performed under an air atmosphere, although the conversion rate was slightly lower (Table 1, entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst-free attempt was also carried out and proved the essential role of the main-group catalysis and confirmed no leaching of the alkali species from the glassware, which could act as potential co-catalysts (entry 2, the results verified after 24 h). 50 The reaction can be also performed under an air atmosphere, although the conversion was slightly lower (entry 3). The use of MeCN as a solvent was critical, as demonstrated by the lack of conversion observed in toluene and dioxane (entry 12 and 13) and the lower yield (75%) obtained in THF (entry 11).…”
mentioning
confidence: 99%